Improving Critical Thinking Ability Class IV Students Flat Building Material CTL Model SDI Al Mashduqie - Nadhyva Maulida Farih; Adisti Istivari Wahyudi Adisti Istivari Wahyudi; Fitratuz Zahroh; Agung Setyawan; Nurul Widad Ramadina (Yayasan Pondok Pesantren Nurul Islam Mojokerto, 2024)
Through the Contextual Teaching and Learning (CTL) approach, students are directed to relate mathematical concepts to the real situation around them. This helps strengthen their understanding of these concepts and builds critical thinking skills more deeply. At the beginning of the first cycle, researchers applied the Contextual Teaching and Learning (CTL) learning model by using group discussion strategies and providing concrete examples of the application of relevant concepts in everyday life. Through interaction in group discussions and examples of practical application, students were expected to develop critical thinking skills and be able to apply these concepts more effectively in everyday life. In the second phase of this cycle, researchers applied the Contextual Teaching and Learning (CTL) model with a focus on improving students' cognitive learning outcomes in Mathematics. Interaction in group discussions guided by the teacher is expected to help students to develop critical thinking skills, improve problem solving skills, and improve their cognitive learning outcomes in Mathematics. Based on a class action research study conducted over 2 cycles, it can be concluded that the application of the CTL model can improve the learning outcomes of fourth grade students of SDI Al Mashduqie.